THE ROLE OF THE LAW IN DEVELOPMENT ACCELERATION TO GENERATE PEOPLE WELL-BEING - Widyawati, Anis (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2020)
The role of law in national development has a strategic role. The state is seen as the primary vehicle for implementing the plans that have been made and the law as a means of translating development goals into applied norms. The results show that the role of law in national development includes law as a tool of social engineering, law as a tool of social control, law as a means of controlling development, law as a means of enforcing justice, and law as a community education. Laws play an important role in national development. Indonesia as a constitutional state has laws that regulate various aspects of state life. Government policies are implemented with the aim of providing welfare. The conclusion in this paper is that the role of law in development has actually begun to appear when decisions made by development planners must be carried out.